FROM SCHILLER'S 'TRILL' TO 'OIL' FROM RUSSIAN HYDROCARBONS - Anatoliy I. Vorobiev; Pavel A. Gudkov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
In conditions of budget deficit and difficulties in capital borrowing on global markets the issue of home borrowing is becoming more and more acute. A derivative profitable both for the government and citizens, who keep their savings in Russian banks, could become a partial solution for the current complicated economic situation in the country. The article shows technologies of creating a new finance tool, provides the analysis of its profitability and service costs in comparison with the most popular units of investment or loan. On the basis of research the authors worked out forecasts of the oil market situation for the next 10 years, which serves as a foundation of the derivative being proposed.